Churches as auditoria investigating the relationship between subjective and objective acoustic parameters in catholic churches in Davao City - Aquino, Steffanie N.; Pernes, Nory Loyd N.
This study reports on subjective and objective acoustical field measurements made in a survey of 9 Catholic churches in Davao City built in the 1980s up to present. Architectural parameters from the physical dimensions of the church were observed. Objective acoustical measurements (Reverberation Time, Early Decay Time, Clarity, Definition, Center Time and Loudness) were taken in each church and a number of 15 listeners were asked to judge the subjective quality of music. The listeners in each church evaluated live music performances at similar locations in each room. Evaluation sheets were used to record the listeners? overall impressions of room acoustic quality. The evaluated results consisted of Subjective Acoustical Parameters: Loudness, Reverberance, Intimacy, Envelopment, Directionality, Balance, Clarity Echoes and Background Noise. This paper concentrated on the relationships of the subjective parameters with the architectural features of the churches and objective parameters were also correlated with the existing architectural parameters of the church. Correlation analyses and statistical modelling identified significant relationships among the measures. For instance, linear correlation coefficients (| R I ) of 0.8-0.9 were found for the relationships: Volume and Reverberation time/Early Decay time, and Clarity and Height of nave. The results taken from regression analyses of variables with significant relationships were used as a basis for designing an acoustically-improved Catholic church. The assumed result of reverberation time and the derived formula from the regression analyses was used to determine the interior volume of the church. Interior measurement of height of nave was derived from the formula which affects the clarity of music.
Thesis (BS Architecture) -- University of the Philippines Mindanao, 2014